Study on characterization and physicochemical properties of new natural fiber from Phaseolus vulgaris. Issue 7 (3rd October 2019) - Gurukarthik Babu, B.; Prince Winston, D.; SenthamaraiKannan, P.; Saravanakumar, S.S.; Sanjay, M. R.
ABSTRACT: Characterization of new natural fibres from various parts of plants have become increasingly popular not only in textile industries, automotive sector, electrical applications, and construction industries, but in various industrial applications because of their versatile characteristics, availability, biodegradability and providing sustainable solutions to support technical innovation. This study aimed to determine the characterization and physicochemical properties of Phaseolus vulgaris fibers (PVF) by Thermo gravimetric analysis (TGA)/DTG, X-Ray Diffraction analysis (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). Eventually, fourier transform analysis and XRD analysis of PVFs demonstrated the presence of cellulose with a crystallinity index of 43.01%. The surface morphological analysis was observed and reveals that PVFs contain rougher surfaces, which would be favourable to develop good bonding with the matrix for making composites.